Oxidative degradation of sulfamethazine by manganese oxide supported biochar activated periodate: Effect and mechanism - Shuheng Hu; Hao Lu; Wenyi Xie; Shaohua Cao; Jiaqi Shi; Yang Guo; Xin Zhu; Zimu Xu; Han Gao (Ecotoxicology and Environmental Safety)
In this study, manganese oxide supported biochar (MBC) was used as a catalyst of periodate (PI) for the oxidative degradation of sulfonamide antibiotic sulfamethazine (SMZ). The degradation rate of 10 mg/L SMZ reached 99 % in 60 min in the MBC/PI system, and the optimal condition was pH 3.5, 0.12 g/L of MBC, and 0.17 mM of PI. Combined with quenching experiment and electron paramagnetic resonance (EPR) characterization, it was determined that the reactive oxygen species (ROS) participating in the reaction include iodate radical (IO3∙), singlet oxygen (1O2), and hydroxyl radical (∙OH). ROS, Mn(III) and electron transfer are three crucial SMZ removal mechanisms in MBC activated PI system, and the conversion process of reactive species was deduced. The manganese redox cycles, oxygen-containing functional groups on MBC surface, and BC-O-Mn(II) complex participated in reactive species production. The loading of manganese oxide increases the number of oxygen-containing functional group on the surface of BC, and BC-O-Mn(II) complex formation resulted in the higher catalytic activity compared with BC. Ten SMZ oxidative products and four transformation pathways was identified. This study provided an efficient and practical method to remove sulfonamide antibiotics and revealed its theoretical mechanism.